CODE MIXING IN THE CLASSROOM INTERACTION OF SMKN 7 MEDAN - Muhammad Azmi; Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The objective of this study is to find out the type of code-mixing used by the teacher and students and the factors causing the teacher and students mix the language in classroom interaction. Code-mixing is a bilingualism phenomenon which has become very popular in society. It is used to prevent misunderstanding such the teacher and students in classroom interaction. This study was conducted by using descriptive qualitative design. The subjects of this study were the teacher and students from tenth grade of hotel accommodation in SMKN 7 Medan. The data were collected by recording the teacher and students’ utterances in classroom interaction, the interview result of teacher and questionnaire of students. From the research, it was found the type of code-mixing used by the teacher and students were word insertion, phrase insertion, and clause insertion. All of data belongs to outer code-mixing and the factors causing teacher did the code-mixing were speaker partner, bilingual or multilingual, and absence of vocabulary. And for the students, according to the percentages of their questionnaire result the data shows that out of 24 students 45,8% of them chose speaker partner as their reason did the code mixing, 8,3% chose bilingual or multilingual, and 45,9% chose absence of vocabulary.